Microstructure and texture evolution of pure niobium in cold-drawn Mg+B/Nb/Cu wires - Sang-Yong Park; Jong-Beom Lee; Ha-Guk Jeong (Materials Research Express, 2022)
In this study, Mg+B wires were prepared by powder in tube method using Nb and Cu tubes as barrier and sheath, respectively, followed by cold drawing. Microstructural, textural, and mechanical properties of the Nb barrier at different drawing strains ( ε _d ) were investigated. The results showed that the Nb barrier demonstrated a saturation hardness of 159.4 HV. The microstructure of the Nb barrier became elongated along the drawing direction increasing ε _d . Sub-grains existing inside the deformed grains rotated from low-angle grain boundaries to high-angle grain boundaries and developed into new grains. The main textural components of the Nb barrier were {111}  γ -fiber and {hkl}〈110 〉  α -fiber. Recrystallized grains exhibited a low maximum orientation distribution function intensity, weak {100}〈110 〉  α -fibers, and strong {111}〈110 〉  γ -fibers as compared to those of the deformed grains. The relationship between the microstructure evolution and mechanical properties of the Nb barrier and the changes in the cross-sectional area fractions of the materials constituting the Mg+B composite wire are discussed. The current study provides details about the misorientation profile inside deformed grains and continuous dynamic recrystallization mechanism of the cold-drawn Nb barrier.